STUDENTS WRITING EMAILS TO FACULTY: AN EXAMINATION OF E-POLITENESS AMONG NATIVE AND NON-NATIVE SPEAKERS OF ENGLISH - Sigrun Biesenbach-Lucas (Language Learning and Technology)
This study combines interlanguage pragmatics and speech act research with computer-mediated communication and examines how native and non-native speakers of English formulate low- and high-imposition requests to faculty. While some research claims that email, due to absence of non-verbal cues, encourages informal language, other research has claimed the opposite. However, email technology also allows writers to plan and revise messages before sending them, thus affording the opportunity to edit not only for grammar and mechanics, but also for pragmatic clarity and politeness.The study examines email requests sent by native and non-native English speaking graduate students to faculty at a major American university over a period of several semesters and applies Blum-Kulka, House, and Kasper’s (1989) speech act analysis framework – quantitatively to distinguish levels of directness, i.e. pragmatic clarity; and qualitatively to compare syntactic and lexical politeness devices, the request perspectives, and the specific linguistic request realization patterns preferred by native and non-native speakers. Results show that far more requests are realized through direct strategies as well as hints than conventionally indirect strategies typically found in comparative speech act studies. Politeness conventions in email, a text-only medium with little guidance in the academic institutional hierarchy, appear to be a work in progress, and native speakers demonstrate greater resources in creating e-polite messages to their professors than non-native speakers. A possible avenue for pedagogical intervention with regard to instruction in and acquisition of politeness routines in hierarchically upward email communication is presented.